Bases neurais da ansiedade em modelo animal de pós-menopausa - Luciana Cosenza Castro (2017)
In addition to the hormonal changes, cognitive deficits, hot flashes and mood disorders are commom during the menopause, being anxiety one of the most common. However, it is still to be determined the neurobiological basis of menopause-induced anxiety. In the present study, we validated an animal model of postmenopausal anxiety. We also verified the pattern of Fos expression in brain areas related to anxiety neural circuits, after exposuring animals to a highly anxiogenic event. Our results demonstrated that 12 weeks of ovariectomy (OVX) led to weight gain and triggered anxious-like behaviors measured through distinct behavioral paradigms in C57BL/6 female mice. We also showed that the acute treatment with diazepam had anxiolytic effect in the OVX model, without exerting a sedative effect in any of the tests performed. Interestingly, we observed that Fos expression in potentially anxiogenic areas are increased in OVX females. In contrast, sensory processing areas, such as amygdala and hippocampus, showed lower Fos expression in naïve OVX animals. In addition, the pattern of neural activation in response to anxiogenic event was different in OVX females compared to control animals. Taken together, our results indicate that the OVX model is appropriate for the study of postmenopausal-induced anxiety and shed light on the neural basis of menopause-induced anxiety.